2020
DOI: 10.1002/cad.20351
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Language Development at Age 4–6 Years in Children HIV‐Exposed But Uninfected Compared to Those HIV‐Unexposed and to Children Living With HIV

Abstract: Perinatal HIV infection is associated with delayed neurocognitive development, but less is known about children perinatally HIV‐exposed but uninfected (CHEU). We compared cognitive and language outcomes in 4–6‐year old CHEU versus children HIV‐unexposed and uninfected (CHUU) and children living with HIV (CLHIV). We enrolled 1,581 children (77% of the child population) in five communities in KwaZulu‐Natal, South Africa. Children completed: Grover‐Counter Scale of cognitive development, sub‐scales of the Kaufman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…While studying child cognitive and language outcomes by HIV exposure status in wave 1, Gruver et al [ 15 ] noted that for all outcome measures, HIV-exposed but uninfected children and HIV-unexposed children had comparable scores, while HIV infected children had significantly lower cognitive and language scores. Additionally, in wave 1, Ajayi et al [ 16 ] found that children with low cognitive scores were more often stunted, had no preschool education, and came from areas less favorable in terms of local infrastructure, access to employment, and arable land.…”
Section: Resultsmentioning
confidence: 99%
“…While studying child cognitive and language outcomes by HIV exposure status in wave 1, Gruver et al [ 15 ] noted that for all outcome measures, HIV-exposed but uninfected children and HIV-unexposed children had comparable scores, while HIV infected children had significantly lower cognitive and language scores. Additionally, in wave 1, Ajayi et al [ 16 ] found that children with low cognitive scores were more often stunted, had no preschool education, and came from areas less favorable in terms of local infrastructure, access to employment, and arable land.…”
Section: Resultsmentioning
confidence: 99%
“…However, if a test was not administered and the child was tested prior to the study assessment, then their HIV status was assigned as reported by the primary caregiver. Child HIV status was included because of both its direct and indirect impacts on a child's social, cognitive, and physical development [26,39,40]. Child SDQ baseline prosocial score was included because the impact of primary caregiver mental health disorders on the prosocial scale may vary by a child's initial prosocial score.…”
Section: Covariates (Assessed At Wave 1)mentioning
confidence: 99%
“…5-10 Importantly, cognitive development is also affected in pediatric HIV, where infants and young children with HIV do not perform, as well as their HIV-exposed or HIV uninfected peers. 11-14 ART remains the mainstay of treatment for HIV-associated cognitive disorders in both adults and children. 15 As ART has become more widely available, the prevalence of HIV-associated cognitive impairment has generally decreased, 16-18 yet at an individual level, it remains an important source of morbidity for PWH.…”
Section: Hiv: History and Current Burdenmentioning
confidence: 99%